Analysis Of The Choice Of Fine As An Alternative Punishment In Criminal Offences In Rantauprapat District Court (Decision Study Number: 826/Pid.C/2024/PN.Rap) - Ahmad Raja HP; Zainal Abidin Pakpahan; Nimrot Siahaan (CV. AFDIFAL MAJU BERKAH, 2025)
The choice of fines as an alternative punishment in a criminal act regulated in legislation, but rather an inseparable part of the substance or material of the legislation itself, where judges rarely impose fines on defendants, even though fines are also a solution for the application of criminal law, this has been regulated in Article 10 of the Criminal Code, one of which mentions fines as part of a criminal act. The problem in this study is how the judge's considerations in deciding criminal fines contained in criminal cases, and how to apply criminal sanctions to perpetrators of criminal acts contained in the decision of criminal case Number: 826 / Pid.C / 2024 / PN.Rap., and the method in this study is normative juridical, with a case study approach, by drawing deductive conclusions. The results of this study are the judge's considerations in deciding criminal cases of fines contained in criminal cases, in fact the judge in making a decision has carried out legal considerations, so the judge will first draw the trial facts and is a cumulative conclusion from the statements of witnesses, the defendant's statement, and evidence submitted and examined in court, which is oriented to the dimensions of the locus and tempus delicti of the crime committed, after the trial facts are stated, in the decision the judge will consider the elements (bestenddelen) of the crime that has been charged by the prosecutor or public prosecutor which has a correlation between the facts of the crime charged and the elements of the defendant's guilt that will be sentenced to a fine, and the judge in imposing a fine through his considerations is very limited by the rules of punishment, because the judge has the freedom to determine the type of punishment as contained in Article 10 of the Criminal Code, be it imprisonment, confinement and or a fine. and the application of criminal sanctions for the defendants as in the decision of case Number: 826 / Pid.C / 2024 / PN.Rap. where the judge sentenced the defendant by applying Article 364 of the Criminal Code by adjusting to Perma Number 02 of 2012 concerning the limits of criminal law adjusted in the Criminal Code so that in fact the judge found the defendant had legally and convincingly committed the crime of minor theft as referred to in the Perma and other laws so as to impose a fine on the defendant in the form of a fine in the form of money amounting to Rp. 200,000.00 (two hundred thousand rupiah) with the provision that if the defendants cannot pay it, it will be replaced with imprisonment for 7 (seven) days since the decision was read and has permanent legal force.